Uji Keamanan Ekstrak Etanol Daun Manggis (Garcinia Mangostana L.) Terhadap Tikus Jantan Galur Wistar Dengan Pendekatan Efek Toksisitas Akut: Up and Down Procedure - Delmayana, Mikna; Kaaffah, Silma; Setianingsih, Siti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The use of mangosteen leaves (Garcinia mangostana L.) as traditional medicine is becoming increasingly widespread due to their content of bioactive compounds such as xanthones, flavonoids, and tannins, which are known to have various pharmacological potentials. However, information regarding their safety aspects is still limited, necessitating further research. This study aims to determine the LD50 dose of mangosteen leaf ethanol extract that causes acute toxicity in male wistar rats using the Up and Down Procedure method based on OECD Guideline 425. The study was conducted at the limit test stage using five test animals with a single dose of 2000 mg/kgBW the extract was administered orally to one rat and observed for 24 hours. The results showed that two of the five rats died, but the mortality rate was still below 50%, so the study did not proceed to the main test stage. Based on OECD guideline 425, the LD?? value is estimated to be greater than 2000 mg/kgBW and is classified as mildly toxic according to the GHS (Globally Harmonized System) classification. The conclusion of this study is that the ethanol extract of mangosteen leaves at a dose of 2000 mg/kgBW exhibits low toxicity and has the potential to be safe as a candidate herbal medicine ingredient.